Frontal Brain Activity and Subjective Arousal During Emotional Picture Viewing in Nightmare Sufferers - Michelle Carr (Frontiers in Neuroscience, 2020)
Nightmares are intensely negative dreams that awaken the dreamer. Frequentnightmares are thought to reflect an executive deficit in regulating arousal. Withina diathesis-stress framework, this arousal is specific to negative contexts, thougha differential susceptibility framework predicts elevated arousal in response to bothnegative and positive contexts. The current study tested these predictions by assessingsubjective arousal and changes in frontal oxyhemoglobin (oxyHB) concentrations duringnegative and positive picture-viewing in nightmare sufferers (NM) and control subjects(CTL). 27 NM and 27 CTL subjects aged 18–35 rated subjective arousal on a 1–9scale following sequences of negative, neutral and positive images; changes in oxyHBwere measured by Near-Infrared Spectroscopy (NIRS) using a 2 4 template on thefrontal pole. Participants also completed the Highly Sensitive Person Scale, a traitmarker for differential susceptibility; and completed a dream diary reporting negativeand positive dream emotionality. The NM group had higher trait sensitivity, yet higherratings of negative but not positive emotion in diary dreams. NM compared to CTLsubjects reported higher subjective arousal in response to picture-viewing regardless ofvalence. Dysphoric dream distress, measured prospectively, was negatively associatedwith frontal activation when viewing negative pictures. Results suggest NM sufferersare highly sensitive to images regardless of valence according to subjective measures,and that there is a neural basis to level of trait and prospective nightmare distress. Futurelongitudinal or intervention studies should further explore positive emotion sensitivity andimagery in NM sufferers.